Case Report: Apixaban-Associated Gluteal Artery Extravasation Reversed With PCC3 Without FFP. (August 2016) - Denetclaw, Tina Harrach; Tam, Jacqueline; Arias, Victor; Kim, Rachel; Martin, Christopher
Apixaban, an oral factor Xa inhibitor, has no commercially available assay to measure its activity and no specific antidote. To date, recommendations for managing bleeding associated with apixaban are based on studies with animal models and healthy volunteers (who do not have identified thrombogenic risk factors) and expert opinion. No clinical experience has been published in the literature. Ideally, apixaban would be reversed sufficiently to stop a perilous bleed without producing more thrombogenic risk than the patients' underlying risk factors. Three-factor prothrombin complex concentrate (PCC3) is the least thrombogenic among the suggested reversal agents. Fresh frozen plasma (FFP) is sometimes recommended to add to PCC3, but it adds considerable volume. We describe successful management of an active left gluteal arterial extravasation due to trauma and associated apixaban, in a patient with aortic stenosis and atrial fibrillation, by administration of PCC3 alone, without the added volume of FFP.